Application of FFT and KNN Methods for the Process of Identifying Sound Signals - Yunitasari, Yessi; Saifulloh, Saifulloh; Harly, Daniswara Andhika Putra (IC-ITECHS, 2024)
Everyone has a different kind of voice. Sound is a unique thing and has a certain range of frequencies and intensity of sound that can and cannot be heard by humans. we can detect important characteristics of the sound. The Fast Fourier Transform (FFT) algorithm is an algorithm for calculating Discrete Fourier Transform (DFT). Process of Identifying Sound Signals beginning with the sound data was preprocessed, feature extraction using FFT, classification using KNN and finding the nearest distance using the Euclidean distance method, an accuracy result of 79% of the tested data was obtained.